Dynamic control of construction supply chain to improve labor performance - Moon, S.; Rahnamayiezekavat, Payam; Bernold, L. (American Society of Civil Engineers, 2015)
One of the critical tasks in the construction industry is to accomplish the required levels of quality. In considering the quality as a managerial target, former methodologies stipulated that the ultimate goal should be focused on final quality. However, with the advent of total quality management, the dynamic approach began to grab the attention of the research field. The goal of this research is to present a proactive concept of quality control that is holistic in nature, defining quality as a function of process waste generated along the construction supply chain. To verify the proposed method, the field testing in this paper discusses the prefabricated rebar supply system of an actual construction site in Kensington, New South Wales, Australia. The high quality of rebar supply ensured by the master-bundle concept enabled the steel fixers to increase their productive time from 31.5 to 77.4%. As expected, this radical change was accompanied by a drastic reduction of process waste from 45.5 to 6.2%. The realization of these substantial performance improvements will rest on the industry's ability to adopt mutually supportive relationships and agile communication channels across the supply chain.